1998
DOI: 10.1038/sj.bjp.0701994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atrial natriuretic peptide and cyclic GMP phosphodiesterase inhibition on collagen synthesis by adult cardiac fibroblasts

Abstract: 1 Cardiac ®broblasts play an important role in the pathophysiology of cardiac remodelling induced by hypertension and myocardial infarction by undergoing proliferation and depositing extracellular matrix proteins such as collagen. We have examined the eects of atrial natriuretic peptide (ANP) on proliferation and collagen synthesis by adult rat and human cardiac ®broblasts in culture. 2 In cells from both species radioligand studies using 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…Increased interstitial fibrosis can be explained by paracrine mechanisms, since α 1 -ARs are not expressed in cardiac fibroblasts (57). First, ANF induction was markedly less in the ABKO after TAC (Figure 4), and the natriuretic peptides inhibit fibrosis by direct effects on fibroblasts (58)(59)(60)(61)(62). Thus, impaired upregulation of ANF could partly explain increased fibrosis.…”
Section: Figurementioning
confidence: 99%
“…Increased interstitial fibrosis can be explained by paracrine mechanisms, since α 1 -ARs are not expressed in cardiac fibroblasts (57). First, ANF induction was markedly less in the ABKO after TAC (Figure 4), and the natriuretic peptides inhibit fibrosis by direct effects on fibroblasts (58)(59)(60)(61)(62). Thus, impaired upregulation of ANF could partly explain increased fibrosis.…”
Section: Figurementioning
confidence: 99%
“…Early in the 1990s, atrial natriuretic peptide (ANP), an endogenous hormone that is released by the heart in response to myocardial stretch and pressure overload, was found to inhibit collagen synthesis in cardiac fibroblasts via activation of membrane guanylyl cyclase receptors, and increase in intracellular cGMP levels. 13 Recent evidence shows that endogenous ANP and TGF-␤ expression are both upregulated in heart with pressure overload, 14 and ANP plays an important counterregulatory role against TGF-␤-induced cardiac hypertrophy, remodeling, and fibrosis. 8,14,15 In this issue of Circulation Research, Li et al 16 studied the molecular mechanisms of the counterregulatory effects of ANP/cGMP/protein kinase G (PKG) signaling on activated TGF-␤-induced Smad signaling in cardiac cells.…”
Section: A Key Antifibrogenic Mechanism Of Atrial Natriuretic Peptidementioning
confidence: 99%
“…In vitro studies demonstrated inhibitory effects on proliferation of vascular smooth muscle cells and CMCs as well as extracellular matrix secretion of cardiac fibroblasts (7)(8)(9). Genetic models revealed insight into the complementary role of these NP with respect to regulation of myocardial structure.…”
mentioning
confidence: 99%